(untitled) (European Journal of Interdisciplinary Research and Development, 2024)
The article is devoted to the development and application of AI in the financial market, including the definition of AI, its types, main AI technologies and trends in their development. It also discusses the use of AI in certain sectors of the financial market, the conditions for the development of AI technologies, and the possible risks of introducing AI by financial organizations. Special attention is paid to a review of global trends in AI regulation.